2020
DOI: 10.1002/cam4.3136
|View full text |Cite
|
Sign up to set email alerts
|

Serine‐227 in the N‐terminal kinase domain of RSK2 is a potential therapeutic target for mantle cell lymphoma

Abstract: RSK2 is a serine/threonine kinase downstream signaling mediator in the RAS/ERK signaling pathway and may be a therapeutic target in mantle cell lymphoma (MCL), an almost incurable disease subtype of non‐Hodgkin lymphoma. In this study, serine‐227 (RSK2 Ser227 ) in the N‐terminal kinase domain (NTKD) of RSK2 was found to be ubiquitously active in five MCL‐derived cell lines and in tumor tissues derived from five MCL patients. BI‐D1870, an inhibitor specific to RSK2‐NTKD, caused RSK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In addition, with these growth inhibitory effects, treatment with BI-D1870 repressed the phosphorylation of RSK2 Ser227 , while treatment with ipatasertib for 48 h exerted the optimal inhibition of AKT activity as shown by the dephosphorylation of PRAS40 Thr246 , which is the substrate of AKT. Unlike other cancers [ 33 , 34 , 35 , 36 ], both BI-D1870 and ipatasertib showed no cross-reaction to their respective target molecules. In addition, the combination of the two agents did not result in further inactivation of RSK2 and AKT compared with the effect induced by a single agent in the two HMCLs ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, with these growth inhibitory effects, treatment with BI-D1870 repressed the phosphorylation of RSK2 Ser227 , while treatment with ipatasertib for 48 h exerted the optimal inhibition of AKT activity as shown by the dephosphorylation of PRAS40 Thr246 , which is the substrate of AKT. Unlike other cancers [ 33 , 34 , 35 , 36 ], both BI-D1870 and ipatasertib showed no cross-reaction to their respective target molecules. In addition, the combination of the two agents did not result in further inactivation of RSK2 and AKT compared with the effect induced by a single agent in the two HMCLs ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 88%
“…WB analysis was performed as previously stated ( Supplementary Information ) [ 5 , 23 , 29 , 30 , 32 , 33 ]. The antibodies used are also described in Supplementary Information .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSK2, a kinase downstream to RAS-MAPK signaling, was frequently found to be constitutively active in the MCL cell line and primary samples, independently from RAS/MEK/ERK activation. BI-D1870, a specific inhibitor of RSK2 N-terminal kinase domain (NTKD), induced growth inhibition and apoptosis in MCL lines, suggesting RSK2 NTKD as a potential therapeutic target in MCL [190].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Matsumura‐Kimoto et al demonstrated the potential of a combination of the serine/threonine kinase ribosomal protein S6 kinase (RSK2) and the BTK inhibitor ibrutinib. The inhibition of RSK2 was reported to affect downstream proteins involved in the BCR signalling pathway such as BLNK and CD19, as well as proteins from other pathways, blocking the B‐cell pathogenesis [80].…”
Section: Btk and Immunitymentioning
confidence: 99%